Al-Qur’an dan Relasi Antar Umat Beragama; Diskursus Tentang Pendidikan Pluralisme Agama di Indonesia - Kamarusdiana Kamarusdiana (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract:The issue of diversity in religion is a social fact that has continued to experience conflict shocks lately. Not without reason, the conflict occurred on the grounds of sentiment towards other religions. This has an impact on the disruption of the stability of relations between religious groups. The discourse of religious pluralism is an alternative in overcoming this problem. Grounding religious pluralism is the right effort by not injuring religious values. Islam actually provides a clear explanation in the Koran about building a tolerant relationship in religion. This article will explain and provide an explanation of Islamic values in the Qur'an as an effort to develop religious pluralism that needs to be represented in a plural social context. It is hoped that with this, the harmony between religious people will be realized. Besides that, as a concrete follow-up, an education process is needed about the importance of tolerance in religion.Keywords: Qur'an, Tolerance, Religious Pluralism, Harmony AbstrakIsu keberagaman dalam beragama menjadi fakta sosial yang terus mengalami guncangan konflik belakangan ini. Bukan tanpa alasan, konflik tersebut terjadidengan alasan sentimen terhadap agama lain. Hal ini berdampak pada terganggunya stabilitas hubungan antar umat beragama. Wacana pluralisme agama menjadi alternatif dalam mengatasi masalah tersebut. Membumikan pluralisme agama merupakan upaya yang tepat dengan tidak menciderai nilai-nilai agama. Islam sejatinya hadir memberikan penjelasan yang gamblang didalam Alquran tentang membangun hubungan yang toleran dalam beragama. Tulisan ini akan memaparkan sekaligus memberikan penjelasan nilai-nilai keislaman yang ada dalam Alquran sebagai upaya mengembangkan pluralisme agama yang perlu direpresentasikan dalam konteks sosial yang plural. Diharapkan dengannya, akan terwujud kerukunan antar umat beragama.Selain itu, sebagai tindak lanjut yang konkrit dibutuhkan proses edukasi tentang pentingnya toleransi dalam beragama. Kata Kunci: Alquran, Toleransi, Pluralisme Agama, Kerukunan